Effectiveness of micro-dosing of lime on selected chemical properties of soil in Banja District, North West, Ethiopia - Yenesew Selomon Afework; Selassie Yihenew G.; Ejigu Workineh; Abere Tirusew; Lewoyehu Mekuanint; Adegeh Asmare (Open Agriculture, 2024)
Soil acidity significantly impacted the agricultural productivity of Ethiopia. Liming has been used as a soil ameliorator, albeit it was not successful due to inadequate availability, high cost, and poor infrastructure for lime transportation to the required agricultural land area. Hence, soil amendment with a minimum amount of lime application is a viable option to improve agricultural productivity sustainably. Therefore, this study aimed to investigate the effectiveness of micro-dosing lime on selected chemical properties of acidic soil in North West, Ethiopia. Three lime application methods and eight treatment approaches were used in the field experiment employing a randomized complete block design with four replications. Independent soil samples were collected before and after liming and analyzed for selected chemical properties. Data were analyzed by analysis of variance using SPSS version 22.0 and SAS 9.3. The application of lime had a significant impact (p < 0.01) on the selected soil chemical properties. Micro-dose application of lime efficiently affected the selected soil chemical properties. The results showed that water pH, available phosphorus, cation exchange capacity, and organic carbon exhibited a considerable increase per kg of applied lime: 2.5 × 10−3, 101.3 × 10−3 (mg kg−1), 160 × 10−3 (Cmol(+) kg−1), and 3 × 10−3%, respectively. Conversely, exchangeable aluminum and exchangeable acidity decreased per kg of applied lime by 7.8 × 10−3 (Cmol(+) kg−1) and 12.2 (Cmol(+) kg−1) × 10−3, respectively. Therefore, the micro-dosing lime application proved to be more effective in influencing these soil properties than other application methods, emphasizing its potential as a valuable soil amendment strategy for small-scale farming.